2020
DOI: 10.2147/dddt.s258651
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Median Effective Dose of Oxytocin Needed to Prevent Uterine Atony During Cesarean Delivery in Elderly Parturients</p>

Abstract: Purpose Oxytocin is the first-line agent to prevent and treat uterine atony during cesarean delivery (CD). We compared the effective dose in 50% of the parturients (ED 50 ) of a prophylactic oxytocin bolus during CD in young (<35 years) and old parturients (≥35 years) using Dixon’s up-and-down method. Patients and Methods Twenty-eight young parturients (young group) and 25 old parturients (old group) undergoing CD under combined spinal-epidura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The simplification/depletion of such CCC networks in the aging myometrium may cause a decline in nerve impulse transmission and decreased contractility essential for pregnancy and labor. Our findings suggest that the decreased contractile potential during myometrial aging may justify why older parturients have longer labors 44 and require higher dosages of oxytocin for third-stage labor to prevent uterine atony 45 .…”
Section: Discussionmentioning
confidence: 84%
“…The simplification/depletion of such CCC networks in the aging myometrium may cause a decline in nerve impulse transmission and decreased contractility essential for pregnancy and labor. Our findings suggest that the decreased contractile potential during myometrial aging may justify why older parturients have longer labors 44 and require higher dosages of oxytocin for third-stage labor to prevent uterine atony 45 .…”
Section: Discussionmentioning
confidence: 84%
“…Of note, some prior studies failed to encounter alterations in the contractile ability of myometrial tissues according to age 57 , while others have noted lower responsiveness to oxytocin stimulation 58 or lower electromyographic activity 16 . Clinical studies have reported that older parturients have longer labors 59 , with higher dosages of oxytocin needed for third-stage labor to prevent uterine atony 60 . In this sense, our findings agree with decreased contractile potential during myometrial aging.…”
Section: Discussionmentioning
confidence: 99%
“…Some prior studies did not find differences in contractile ability in myometrial tissue specimen by maternal age [ 11 , 15 ]; however, others have noted lower responsiveness to oxytocin stimulation [ 42 ] or lower electromyographic activity [ 43 ]. Clinical studies report that older parturients have longer labors [ 44 ] and more often need oxytocin in labor [ 8 ], and higher dosages of oxytocin are needed for third-stage labor to prevent uterine atony [ 45 ]. The specific reasons for the differences observed by studies of vitro contractility studies and clinical outcomes by age prompts further study.…”
Section: Discussionmentioning
confidence: 99%